Real time measurement of household power consumption: solution and potential application - Nguyen, Dinh Luyen; Nguyen, Thi Lan Huong; Nguyen, Viet Tung (Old Journal, 2018)
Currently the efficient use of households being interested research sujet in the world not only is occupped 30% to 40% of electricity consumption, but also that is the new and potential research topic. This article present an household electricity power measurement solution in real time. The experiment results are demonstrated that our solution can engage energy consumption with applicances. Moreover the user can understand their consumption data, relate it to concrete activities in their life, can discover there are some waste energy and can act in a more sustainable way.